Russian Intelligentsia in the Socio-Political Transformations of the XX Century: Between Ideals, Virtuality and Creation Reality - Chernoperov, Vasiliy Lvovich; Usmanov, Sergey Mikhailovich (International Review of Management and Marketing, 2016)
The article analyzes the participation of the Russian intelligentsia in socio-political transformations in the contemporary world. It analyzes the problems and contradictions of the virtual and the real in the intellectuals' consciousness and activities. The authors present a new variation model of the Russian intelligentsia participation in public and political life, which includes three basic types of interaction between intellectuals and the authorities: "entering the authority", "eternal confrontation" and "ivory tower". The authors conclude that for Russian intellectuals in their attitude both to the authorities and to the society, the main criterion for self-determination and motivation in their social action is the division into "ours" and "strangers". Keywords: Russian intellectuals, modern world, ideals virtuality, creation reality, JEL Classifications: B31; I29; Z10